Answer:
smh
Step-by-step explanation:
too ez is the answer is 12421418258475172583521838716523/12312313123651253612534
f(x) = 2x - 1
To obtain a function we require values of x for x = 3, 4, 5 , 6, .....
The output appears to increase in steps of 2
3 → 5
4 → 7
5 → 9
6 → 11
Looking at the consecutive values of y we should see that these are twice the corresponding value of x subtract 1
f(x) = 2x - 1 ← is a possible function
checking the values for x in the input
f(3) =(2 × 3 ) - 1 = 5
f(4) = (2 × 4 ) - 1 = 7
f(6) = (2 × 6 ) - 1 = 11
f(11) = (2 × 11 ) - 1 = 21
Answer:
i dont know
Step-by-step explanation:
ed
Answer:
$16.35
Step-by-step explanation:
15 x 1.09 = 16.35
Answers:
a = 2
b = 3
=======================================================
Explanation:
Plug in x = 0 and y = 2 to find that
y = a*b^x
2 = a*b^0
2 = a*1
2 = a
a = 2
Then plug in x = 3 and y = 54 to determine the value of b
y = a*b^x
y = 2*b^x
54 = 2*b^3
2b^3 = 54
b^3 = 54/2
b^3 = 27
b = (27)^(1/3)
b = 3
So we have y = a*b^x update to y = 2*3^x